Willingness to pay for reliable power in the presence of resource depletion: the case of groundwater and electricity in Tamil Nadu. (1st January 2014) - Gajanan, Shailendra N.; Chandramohan, B.P.; Babu, N. Suresh
Using contingent valuation methodology, we present results for farmers' willingness to pay for reliable power, for a sample of 450 farmers in Tamil Nadu, India. We find that small and marginal farmers place a positive value to reliable power. We derive these estimates in a context where electric power has been made available for free, and where ground water levels have reached extremely low levels. We base our motivation from a theoretical model on strategic democracy, which arises when voters and political parties play a game in which agents maximise their individual returns, given the actions of other players. Given the incentives of politicians and voters, we find natural resource depletion as an equilibrium outcome. Strangely this arises not because private markets fail, but because the state behaves as an agent in the market place. Interestingly, we find that farm size and WTP estimates are negatively related across all models.